Acetyl‐coenzyme A carboxylase inhibition reduces de novo lipogenesis in overweight male subjects: A randomized, double‐blind, crossover study. Issue 2 (5th July 2017) - Stiede, Kathryn; Miao, Wenyan; Blanchette, Heather S.; Beysen, Carine; Harriman, Geraldine; Harwood, H. James; Kelley, Heather; Kapeller, Rosana; Schmalbach, Tess; Westlin, William F.
Abstract : NDI‐010976, an allosteric inhibitor of acetyl‐coenzyme A carboxylases (ACC) ACC1 and ACC2, reduces hepatic de novo lipogenesis (DNL) and favorably affects steatosis, inflammation, and fibrosis in animal models of fatty liver disease. This study was a randomized, double‐blind, placebo‐controlled, crossover trial evaluating the pharmacodynamic effects of a single oral dose of NDI‐010976 on hepatic DNL in overweight and/or obese but otherwise healthy adult male subjects. Subjects were randomized to receive either NDI‐010976 (20, 50, or 200 mg) or matching placebo in period 1, followed by the alternate treatment in period 2; and hepatic lipogenesis was stimulated with oral fructose administration. Fractional DNL was quantified by infusing a stable isotope tracer, [1‐ 13 C]acetate, and monitoring 13 C incorporation into palmitate of circulating very low‐density lipoprotein triglyceride. Single‐dose administration of NDI‐010976 was well tolerated at doses up to and including 200 mg. Fructose administration over a 10‐hour period stimulated hepatic fractional DNL an average of 30.9 ± 6.7% (mean ± standard deviation) above fasting DNL values in placebo‐treated subjects. Subjects administered single doses of NDI‐010976 at 20, 50, or 200 mg had significant inhibition of DNL compared to placebo (mean inhibition relative to placebo was 70%, 85%, and 104%, respectively). An inverse relationship between fractional DNL and NDI‐010976 exposure was observed with >90% inhibition of fractional DNL associated with plasma concentrations of NDI‐010976 >4 ng/mL. Conclusion : ACC inhibition with a single dose of NDI‐010976 is well tolerated and results in a profound dose‐dependent inhibition of hepatic DNL in overweight adult male subjects. Therefore, NDI‐010976 could contribute considerable value to the treatment algorithm of metabolic disorders characterized by dysregulated fatty acid metabolism, including nonalcoholic steatohepatitis. (Hepatology 2017;66:324–334).